Psychopathology, physical complaints and risk behaviours among youths who were victims of documented childhood maltreatment, and youths without identification: from methodological issues to research data - Pinto, Ricardo (2013)
Tese de doutoramento em Psicologia (ramo de conhecimento em Psicologia da Saúde)